Investigating the value of personal branding on LinkedIn for marketing graduates entering employment in the advertising industry. - Monareng, Lerato (The IIE, 2020)
This study aimed to explore the value of personal branding on LinkedIn as a professional social networking site specifically for marketing graduates entering the advertising industry. Evidence suggests that most graduates are currently not utilising the full potential that LinkedIn offers for their personal brand (McCabe, 2017). The study seeks to enlighten marketing graduates about the expectation’s recruiters have about their personal brand on LinkedIn by evaluating if there are similarities between their perceptions and recruiters’ expectations. The researcher achieved this by conducting in-depth interviews with recruiters and analysing LinkedIn profiles of marketing graduates which helped gain in-depth understand of the research problem. The findings are that marketing graduates take the effort to develop a personal brand on LinkedIn but do not take the extra measures to promote themselves on the platform.
Keywords: Social network; Social networking sites (SNS); Personal brand; Recruitment; Social network platform; Social media; Brand identity